As geografias da Geografia - Raimundo Nonato Junior (Confins)
This is the presentation of the section “The geographies of geography” in the Confins journal, presenting the fundamental elements of the research, the foundations and the first theoretical-methodological considerations in this regard. This introductory article launches the epistemological provocation of the project, which aims to analyze the presence of geography in the world based on the diversity of publications that present “what is Geography (and how it is done)” in different contexts.